EFFECTIVENESS OF DIABETIC FOOT EXERCISES USING SPONGES AND NEWSPAPERS ON FOOT SENSITIVITY IN PATIENTS WITH DIABETES MELLITUS - Siti Fadlilah; Adi Sucipto; Nazwar Hamdani Rahil (Belitung Nursing Journal, 2019)
Background: Diabetes mellitus is a critical public health problem, and its prevalence in Indonesia remains high. Diabetes mellitus may cause complications, one of which is neuropathy that can impair foot sensitivity. This requires a treatment by doing diabetic foot exercises using sponges and paper. Objective: To examine the effectiveness of diabetic foot exercise using sponges and newspapers on foot sensitivity in patients with diabetes mellitus. Methods: This is a quasi-experimental study with pretest posttest with a control group research design, which was conducted at Public Health Center Depok III, Sleman Regency, Yogyakarta, Indonesia. An accidental sampling technique was used to select participants, with a total sample of 108 respondents consisting of 36 respondents in a control group, 36 respondents in a sponge group, and 36 respondents in a newspaper group. Data were analyzed using Wilcoxon and Mann-Whitney test. Results: Among the three groups, only those who received foot exercises using sponges and newspapers had a significant effect on foot sensitivity (p <.05). However, there was no significant difference on the effect of foot exercise on foot sensitivity between sponges and newspapers group (p >.05). Conclusion: The use of sponges and newspapers in foot exercise could significantly improve foot sensitivity in patients with type 2 diabetes mellitus. It is therefore recommended for nurses to provide the foot exercise as a part of nursing practice in both hospitals and community health centers.